Environmental determinants of thyroid pathology - Ryabukha, O.I.; Fedorenko, V.I. (Medicni Perspektivi, 2021)
Ecological situation of many countries, including Ukraine, is characterized by progressive anthropogenic and technogenic pollution, which causes growth in thyroid pathology, the share of which is significant in the structure of endocrine diseases. The main causes of thyroid disorders include iodine deficiency in the environment, exposure to a number of widely used chemicals (thyrodisruptors), heavy metal ions. A variety of physical environmental factors are important. A significant increase in thyroid cancer is frequently associated with local or general exposure to ionizing radiation. Prolonged exposure to electromagnetic fields can lead to disorders in the gland’s homeostasis. The functional capacity of the gland is also impaired by unsanitary living conditions, some bacteria and viruses, and improper nutrition. High sensitivity of the gland to external impacts and high social significance of thyroid pathology give grounds to consider the morphofunctional condition of the thyroid gland as a marker of ecological well-being of the environment.